Smoking Therapy: Effective Ways to Stop Smoking in RW 13 Jayagiri, Lembang, Bandung Regency - Kristin Kristin; Hani Triana; Liliek Fauziah; Ira Octavia Siagian; Lidya Maryani; Sundariningsih Sundariningsih (Asosiasi Profesi Multimedia Indonesia, 2024)
One of the healthy living behavior programs is to prevent good smoking behavior in the community. This service aims to increase knowledge about smoking behavior and improve clean and healthy living behavior in RW 13 Jayagiri, Lembang, Bandung Regency. The method used in this service is to use the pre-test method and the delivery of material in the form of counseling, as well as carrying out evaluations. Data collection using questionnaire sheets as evaluation material. The results obtained in this service were obtained distribution based on high school education as many as 16 people (64%), S1 4 people (16%), junior high school 3 people (12%), elementary school 2 people (8%) with ages 10-15 years 2 people (8%), ages 16-20 years 13 people (52%), ages 21-25 years 5 people (20%), ages > 25 years 5 people (20%) The pre-test results on knowledge about smoking behavior are as follows whose knowledge is lacking as many as 13 people (52%), Enough knowledge 9 people (36%), good knowledge 3 people (12%) after counseling the knowledge obtained increased with the results of less knowledge as many as 7 people (28%), enough knowledge 9 people (9%), good knowledge 9 people (36%). So, it can be concluded that there is an influence of knowledge before being given and after counseling on smoking behavior. Therefore, it is necessary to continue socializing about the dangers and risks of smoking behavior to improve clean and healthy living behavior.